Recent progress in the all‐solid‐state flexible supercapacitors. Issue 3 (18th April 2022) - Yang, Yongrui; Zhu, Tao; Shen, Lening; Liu, Yanghe; Zhang, Dong; Zheng, Bowen; Gong, Keven; Zheng, Jie; Gong, Xiong
Abstract: In the past few years, supercapacitors (SCs) have attracted great attention in both academic and industrial sectors due to their high energy storage efficiency, reliable stability, and eco‐friendly process. Flexible solid‐state SCs as one of the ongoing focuses for the development of wearable and portable electronics have become the most promising energy storage devices for the smart power system due to their high power density, fast electrochemical response, high efficiency on the charge‐discharge process, and excellent electrochemical stability. In this study, the recent progress in the electrodes and electrolytes used for approaching high‐performance of the all‐solid‐state flexible SCs is reviewed. We first introduce basic operational principles of various SCs. And then we overview the electrode materials including carbon materials, conducting polymers, transition metal oxides/chalcogenides/nitrides, MXenes, metal‐organic frameworks, covalent‐organic frameworks, and the polymer‐based solid‐state electrolytes in different systems. Afterward, we summarize recent progress in the development of the all‐solid‐state flexible SCs and outlook for future research directions. Abstract : Supercapacitors have attracted great attention in both academic and industrial. In this article, the electrode materials including carbon materials, conducting polymers, transition metal chalcogenides/nitrides, MXenes, metal‐organic frameworks, covalent‐organic frameworks, and the polymer‐based solid‐state electrolytes in different systems are reviewed.